National Health Service (NHS) trust boards adopt statistical process control reporting: the impact of the Making Data Count Training Programme. Issue 4 (30th April 2021) - Riley, Samantha; Burhouse, Anna; Nicholas, Thomas
Abstract : Background: Red, amber, green (RAG) reports persist as the tool most commonly used by NHS trust boards to understand performance and gain assurance, despite statistical process control (SPC) being a more reliable way of presenting data over time. The aim of this study is to report board members' feedback on an educational intervention focusing on the use of SPC in NHS trust performance reports, review the presence of SPC charts in performance reports and explore board members' experience of behavioural changes in their board or fellow board members following the intervention. Methods: A 90-minute board training session in the use of SPC—Making Data Count—was delivered to 61 NHS trust boards between November 2017 and July 2019. This paper describes the approach taken with boards to enable them to understand the limitations of RAG reports and the benefits of using SPC and analyses the extent to which the Making Data Count training has led to boards adopting SPC. The paper provides quantitative analysis of the increase in SPC use across the 61 participating boards, summaries from the board evaluation forms and qualitative reflections of seven senior leaders from four boards who consented to participate in post-training interviews with an independent evaluator. Results: During the period covered by this study, 583 participants of board training provided feedback. 99% of respondents agreed that the training session was a good use of their time. 97% of respondents agreed that participating in the event would enhance their ability to make good decisions. A review of the presence of SPC charts in the board papers of the 61 trusts prior to the board training revealed that 72% contained 0–5 SPC charts. A review of the same trusts' papers 6–12 months after the training revealed a significant increase in the presence of SPC with 85% of reports containing a minimum of six charts. Conclusion: The Making Data Count education intervention has increased the use of SPC in board reports and has had some self-reported impact on individual and collective behavioural changes by board members, including reducing the amount of time wasted by boards discussing insignificant changes in data and providing a clearer focus on those issues requiring board attention. Further research is required to see if this immediate impact is sustained over time and to identify the key enablers and barriers to organisational adoption of SPC by boards in the NHS.